Transfusion Medicine Education for Anesthesiology Residents: A Novel Curriculum - Fatima Aldarweesh MD; William Nicholas Rose MD (Elsevier, 2019)
Transfusion medicine education for anesthesiology residents was an unmet need at our institution. Our goal was to develop a detailed and organized curriculum to introduce the essentials of transfusion medicine to first-year anesthesiology residents during a 3-week shared rotation. Based on our observations and the residents' feedback, the curriculum was modified after each year with the goal of creating a more resident-focused educational experience. Here, we report our 3-year experience of creating, teaching, and revising this curriculum to 35 residents, and we share our detailed curricula and learning aids (including over 100 directing questions for reading assignments) so that the interested reader can begin using them immediately.